The Association Between Time-Varying Wall Shear Stress and the Development of Plaque Ulcerations in Carotid Arteries From the Plaque at Risk Study - Dilba, Kristine; van Dam-Nolen, Dianne H. K.; Korteland, Suze-Anne; van der Kolk, Anja G.; Kassem, Mohamed; Bos, Daniel; Koudstaal, Peter J.; Nederkoorn, Paul J.; Hendrikse, Jeroen; Kooi, M. Eline; Gijsen, Frank J. H.; van der Steen, Anton F. W.; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background and Purpose Shear stress (WSS) is involved in the pathophysiology of atherosclerotic disease and might affect plaque ulceration. In this case-control study, we compared carotid plaques that developed a new ulcer during follow-up and plaques that remained silent for their exposure to time-dependent oscillatory shear stress parameters at baseline. Materials and Methods 18 patients who underwent CTA and MRI of their carotid arteries at baseline and 2 years follow-up were included. These 18 patients consisted of six patients who demonstrated a new ulcer and 12 control patients selected from a larger cohort with similar MRI-based plaque characteristics as the ulcer group. (Oscillatory) WSS parameters (time average WSS, oscillatory shear index (OSI) and relative residence time (RRT)) were calculated using computational fluid dynamics applying the MRI-based geometry of the carotid arteries and compared among plaques (wall thickness>2 mm) with and without ulceration (Mann-Whitney U test) and ulcer-site versus non-ulcer-site within the plaque (Wilcoxon signed rank test). More detailed analysis on ulcer cases was performed and the predictive value of oscillatory WSS parameters was calculated using linear and logistic mixed-effect regression models. Results The ulcer group demonstrated no difference in maximum WSS (9.9 [6.6-18.5] vs. 13.6 [9.7-17.7] Pa, P=0.349), a lower maximum OSI (0.04 [0.01-0.10] vs 0.12 [0.06-0.20] P=0.019) and lower maximum RRT (1.25 [0.78-2.03] Pa-1 vs 2.93 [2.03-5.28] Pa-1), P=0.011) compared to controls. The location of the ulcer (ulcer-site) within the plaque was not always at the maximal WSS, but demonstrated higher average WSS, lower average RRT and OSI at the ulcer-site compared to the non-ulcer-sites. High WSS (WSS>4.3 Pa) and low RRT (RRT<0.25 Pa) were associated with ulceration with an odds ratio of 3.6 [CI 2.1-6.3] and 2.6 [CI 1.54 – 4.44] respectively, which remained significant after adjustment for wall thickness. Conclusion In this explorative study, ulcers were not exclusively located at plaque regions exposed to the highest WSS, OSI or RRT, but high WSS and low RRT regions had a significantly higher odds to present ulceration within the plaque even after adjustment for wall thickness.